Detection of Mycobacterium Tuberculosis DNA in Buccal Swab Samples from Children in Lima, Peru. Issue 11 (November 2020) - Flores, Juan A.; Calderón, Roger; Mesman, Annelies W.; Soto, Martin; Coit, Julia; Aliaga, Juan; Mendoza, Milagros; Leon, Segundo R.; Konda, Kelika; Mestanza, Francisco M.; Mendoza, Carlos J.; Lecca, Leonid; et al.
Abstract : We examined Mycobacterium tuberculosis DNA detection from buccal swab samples collected from children in Lima, Peru. DNA was extracted and amplified via real-time polymerase chain reaction. Sensitivity was 21% (95% confidence interval [CI]: 7%–42%) in 24 culture-confirmed tuberculosis cases and 4.6% (95% CI: 1%–13%) in 65 clinically diagnosed unconfirmed cases. Sensitivity was highest for smear-positive tuberculosis. Specificity was 99% in the 199 controls (95% CI: 96%–100%). Abstract : Supplemental Digital Content is available in the text.